Synthesis and Anti‐HIV Activity of a Series of 6‐Modified 2′, 3′‐Dideoxyguanosine and 2′, 3′‐Didehydro‐2′, 3′‐dideoxyguanosine Analogs. Issue 9 (16th September 2013) - Xie, Lujia; Yang, Xiantao; Pan, Delin; Cao, Yingli; Cao, Mou; Lin, Guichun; Guan, Zhu; Guo, Ying; Zhang, Lihe; Yang, Zhenjun
Abstract In search of potential 2′, 3′‐dideoxyguanosine (ddG) and 2′, 3′‐didehydro‐2′, 3′‐dideoxyguanosine (D4G) prodrugs, a series of 6‐modified ddG, D4G analogs were synthesized and evaluated for their anti‐HIV activities and cytotoxities in cell‐based assays. All analogs showed low cytotoxicities and some of them displayed benign anti‐HIV activities. The active triphosphate forms in vivo, ddGTP and D4TTP, were also synthesized by a novel and facile "one‐pot" method. The recognition of ddGTP and D4TTP by Taq, Therminater DNA polymerase and HIV reverse transcriptase (RT) incorporated in DNA/RNA strands were investigated by a non‐radioactivity method and Km were determined.